Assistance in Implementing an Anti-Corruption School Culture to Realize an Integrity Zone at SMKN 1 Baso - Tiara, Monica; Irwan, Irwan; Rifma, Rifma (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
The mentoring initiative for the Implementation of the Anti-Corruption Culture School at SMKN 1 Baso represents a strategic intervention aimed at strengthening the integrity zone within the educational environment. The program holds substantial urgency, functioning as an early preventive effort against potential corruption by embedding integrity values across all levels of the school community. The initiative was conducted in collaboration with the Association of Vocational School Principals (MKKS) of Agam Regency, with SMKN 1 Baso designated as the pilot institution. The mentoring activities encompassed enhancing anti-corruption literacy among teachers, education personnel, and students; facilitating the development of institutional policies and anti-corruption standard operating procedures (SOPs); and reinforcing an integrity-driven learning ecosystem. The program was carried out over an eight-month period using a Participatory Action Research framework, progressing through seven structured stages including socialization, capacity-building workshops, implementation assistance, and the establishment of supporting integrity infrastructures. The results indicate that the school successfully formulated and enacted anti-corruption SOPs, produced student-led integrity projects, established a ZI Corner and an Integrity Tree, and strengthened collective commitment toward transparency and accountability. These outcomes suggest a measurable increase in integrity awareness and the gradual institutionalization of integrity practices as part of the school’s cultural identity.